Formulation and characterization of butylated hydroxytoluene (BHT) microspheres using natural beeswax as encapsulating material. Issue 4 (12th February 2022) - Gundev, Promita; Chauhan, Komal; Sachdev, Divya; Swer, Tanya Luva
Abstract: Cold‐pressed underutilized oils are rich in polyunsaturated fatty acids and are susceptible to oxidation. This majorly impacts the sensorial shelf life of the oil and causes rancidity. In view of preventing the oxidation and increasing the shelf life, butylated hydroxytoluene (BHT) antioxidant was incorporated. In order to enhance the oxidative stability of underutilized oil, BHT was encapsulated inside the natural and biodegradable beeswax using the emulsion congealing technique. The effect of BHT/beeswax ratios was studied to depict the best encapsulation efficiency, flow properties, and their characteristics were identified via different characterization techniques. The microspheres were spherical in shape and showed high encapsulation efficiency varying from 96.55 ± 1.973% to 99.2 ± 0.983%. The 2, 2 diphenyl‐1‐picrylhydrazyl (DPPH) scavenging activity was highest for Formulation C (69.79 ± 1.037%). Formulation A (1:1) showed first‐order release kinetics and higher thermal stability with enhanced antioxidative potential which can be used in cold‐pressed oils to impart oxidative and storage stability. Practical applications: Butylated hydroxytoluene (BHT) is an antioxidant added to oils to scavenge the free radicals produced during the oxidation of oils. BHT compound is sensitive and unstable at high temperatures that limit its effectiveness. The stability of BHT can be improved via encapsulation methodology, wherein a polymer protects the encapsulated BHT from chemical degradation and helps in its controlled release. The present work involves encapsulating BHT in natural polymer viz. beeswax resulting in BHT‐loaded microspheres with enhanced thermal and oxidative stability. The resultant microspheres can be used for food applications requiring high temperature during baking, extrusion for the development of baked, extruded, or savory food products without compromising the effectiveness of the BHT.